Aktualisasi Proses Pendidikan Nasional pada SILN dalam Asimilasi SIDH Belanda dan SIKL Malaysia - Husni Mubarok; Vina Rosalia Fatma; Nur Aisyah; Alfiyaturrohmah Wulandari; Nilta Hidayah; Fina Ni’matun Najah (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2021)
This study focuses on the teaching and learning process of Indonesian overseas schools (SILN). The purpose of making this article is to find out how the actualization of the national education process in SIDH Belanda dan SIKL Malaysia in assimilation in their country. This type of research is qualitative research. The method used is descriptive document analysis. And based on the analysis of various documents, it was found that the two countries implemented national education into teaching and learning activities. There are similarities and there are differences between the teaching and learning activities of the two countries. There are similarities and differences in the teaching and learning activities of the two countries, which are seen from three aspects, among others, national education in the curriculum, national values in the curriculum, and the strategy for implementing national education. In addion, Learning at Indonesian Overseas Schools (SILN) is also carried out optimally by SILN teachers in facing challenges and obstacles, this learning is carried out in order to realize and implement national education even though in overseas areas and to create smart and quality successors of the nation.